Influência da lastragem e pressão de inflação do pneu de um trator agrícola no seu desempenho operacional trabalhando em solo na capacidade de campo - Alonso, Diego José Carvalho (2016)
The agricultural tractor is present in all stages of agricultural production, from the initial preparation of the soil to the transportation of the final product. Many are the ways for controlling the quality and efficiency of its work, among which we highlight tire pressure and ballasting. However, a determining factor that cannot be controlled is climate, with which the only option is adjusting the tractor to soil moisture to allow better efficiency, but the use of the correct pressure and ballast must provide satisfactory fuel consumption. Thus, this work aimed at evaluating the hourly and specific fuel consumption, draw bar force and slippage of an agricultural tractor using three ballasts and five tire pressures, in soil presenting field capacity of 150 m 3 /m 3 of moisture. The experiment was conducted at the Palmital farm, of the Universidade Federal de Lavras (UFLA), in the municipality of Ijací, Minas Gerais, Brazil, in June of 2016. The soil was adapted to field capacity by means of central pivot and assessed in field by electric field sensor. The tractor used was a A950 Valtra 4x2 TDA, with 95 horsepower (69.8kW), at 2200 rpm, according to norm ISO TR 14396, assembled on diagonal back tires 18.4 – 34 R-1 and front tires 14.9 – 24 R-1. The breaking tractor used was Agrale BX 6110 4x2 TDA, with 105 horsepower (77.2 kW), at 2300 rpm, assembled on diagonal back tires 18.4 – 34 R-1 and front tires 14.9 – R-1. A HBM U1 charge cell of 5 tons connected both tractors in order to assess the force of the draw bar. Fuel consumption was measured by means of an Oval flow meter, while slippage was measured using the marks and times method. The experimental design was completely randomized, assembled in a 5x3 factorial scheme, with 15 treatments and 3 replicates. The results of parameters volume and specific fuel consumption, slippage and draw bar force showed higher efficiency using ballasts 47.5 kN and 44.67 kN, and 110 kPa of back tire pressure and 97 kPa of front tire pressure.